2006
DOI: 10.1007/s00531-006-0107-5
|View full text |Cite
|
Sign up to set email alerts
|

Support for the Giant Wave Hypothesis: evidence from submerged terraces off Lanai, Hawaii

Abstract: The origin of subaerial coral conglomerate deposits on the Hawaiian islands of Lanai and Molokai is controversial, primarily because these deposits are difficult to interpret and the vertical motion of these islands is poorly constrained. Based on bathymetry, dive observations, sedimentary and radiocarbon data from coralline algal dominated deposits from two submerged terraces at -150 and -230 m off Lanai, Lanai has experienced relatively little vertical movement over the last 30 ka. Using internally consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…For example, Webster et al (2007) found a welldeveloped terrace west of Lanai at ~150 m depth tilting at 0.8 m/km toward Hawaii. Ruhe et al (1965) identifi ed this same terrace off Oahu at a mean depth of 107 m with little tilting or warping; they also found that terraces shallower than 107 m were not warped or tilted.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Webster et al (2007) found a welldeveloped terrace west of Lanai at ~150 m depth tilting at 0.8 m/km toward Hawaii. Ruhe et al (1965) identifi ed this same terrace off Oahu at a mean depth of 107 m with little tilting or warping; they also found that terraces shallower than 107 m were not warped or tilted.…”
Section: Discussionmentioning
confidence: 99%
“…Coral conglomerate/boulder deposits and reef limestones have been used as excellent archives that record tsunami generation and propagation (Webster et al, 2007;Imamura et al, 2008), the timing and scale of repeated coseismic uplifts (Ota et al, 1993;Chappell et al, 1996;Sugihara et al, 2003), and sea-level changes (Fairbanks, 1989;Bard et al, 1996), because corals can be accurately dated and because coral and coralline algal assemblages are available to determine depositional environments, especially the paleobathymetry of those deposits (Iryu, 1992;Cabioch et al, 1999;Sagawa et al, 2001). The present study clearly shows that warm temperate carbonates, which consist mainly of annelids, nongeniculate coralline algae, barnacles, and corals, are as useful to reconstruct such geologic events as the tropical carbonates because the depositional ages and environments of those components can be determined with high precision and accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The history of vertical motion of the Maui‐Nui Complex (MNC, consisting of the islands of Lanai, Molokai, Maui and Kahoolawe and their adjacent areas) and the nearby island of Oahu in Hawaii is complex and poorly understood [ Grigg and Jones , 1997; Moore , 2000; Webster et al , 2007]. Rapid subsidence of Hawaii [ Caccamise et al , 2005; Ludwig et al , 1991; Moore and Fornari , 1984; Moore et al , 1996] has been attributed to volcanic loading over the hot spot, whereas observational data from Oahu indicates that it is slowly uplifting [ McMurtry et al , 2010; Muhs and Szabo , 1994].…”
Section: Introductionmentioning
confidence: 99%
“…However, our understanding of the relationship between the vertical plate motions and hot spot dynamics has been hampered by limited observational data with which to test the modeling studies. [3] Gently tilted submarine terraces around the Main Hawaiian Islands have long been recognized and interpreted as former shorelines tilting toward the rapidly subsiding Hawaii [Campbell, 1986;Clague et al, 2000;Moore, 1987;Moore and Campbell, 1987;Moore et al, 1990;Price and Elliot-Fisk, 2004;Webster et al, 2006Webster et al, , 2007. Campbell [1986] identified submerged terraces off Lanai and calculated a subsidence of 1.9 m/kyr for Lanai and 2.4 m/kyr for Hawaii.…”
Section: Introductionmentioning
confidence: 99%